Infant Temperament Profiles, Cultural Orientation, and Toddler Behavioral and Physiological Regulation in Mexican‐American Families. Issue 6 (19th July 2021) - Lin, Betty; Lemery‐Chalfant, Kathryn; Beekman, Charles; Crnic, Keith A.; Gonzales, Nancy A.; Luecken, Linda J.
Abstract : This study sought to (a) replicate infant temperament profiles from predominantly White samples in a sample of low‐income, predominantly first‐generation Mexican‐American families, (b) investigate associations between infant temperament profiles and toddler behavioral and physiological regulation, and (c) explore whether mothers' cultural orientation would moderate those associations. Mothers and infants ( n = 322; 46% male) were assessed during pregnancy and at infant ages 9, 12, and 24 months. Latent profile analysis yielded three temperament profiles that were consistent with those from extant research. Compared to the high positive affect, well‐regulated profile, the negative reactive, low regulated profile was associated with poorer behavioral and parasympathetic (i.e., respiratory sinus arrhythmia) regulation, but associations depended on mothers' Mexican and Anglo cultural orientation.